Leverage, Profitabilitas, Ukuran Perusahaan dan Intellectual Capital Terhadap Nilai Perusahaan F&B di BEI (2020-2024) - Fitriani, Suci; Sandi Yuda, Mulfi; Hardianto, Ade Manggala; Novitasari, Yuli (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2025)
This study aims to examine the effect of Leverage, Profitability, Firm Size, and Intellectual Capital on Firm Value in manufacturing companies within the Food and Beverage subsector listed on the Indonesia Stock Exchange during 2020–2024. A quantitative method was employed using secondary data obtained from annual financial reports. Multiple linear regression analysis was performed, including classical assumption tests, F-test, t-test, and coefficient of determination (R²). The results show that simultaneously the four independent variables significantly influence firm value. Partially, Firm Size has a negative and significant effect, while Leverage, Profitability, and Intellectual Capital have no significant effect. The coefficient of determination (R²) of 0.095 indicates that the model explains only 9.5% of the variation in firm value, with the remaining 90.5% influenced by other factors. These findings highlight the importance of managing firm size and strategically utilizing intellectual capital to enhance firm value.